ANALISIS LUASNYA PENGUNGKAPAN KUANTITATIF PADA INTEGRATED REPORTING DI INDONESIA, MALAYSIA, DAN SINGAPURA - Agnes Febriyanti Febriyanti; Juniati Gunawan (Jurnal Magister Akuntansi Trisakti, 2016)
This study aims to determine how much disclosures can be found on the IR issued by companies in Indonesia, Malaysia, and Singapore that implement International <IR> Framework as a guide. This study uses a total observation of 21 (twenty one) Integrated Reports, consisting of 12 (twelve) IR from Indonesia, 5 (five) IR from Malaysia, and 4 (four) IR from Singapore, where the entire population is used as the research object.Content analysis and descriptive qualitative are used as the chosen methods to explore many information disclosures. The result of this study shows that IR  in Indonesia, Malaysia, and Singapore falls in the high category. This achievement was obtained because the companies that are used as the object of the research (the companies that publish IR) might be are top companies (total assets, capital, business lines, and employees) and have a good reputation. In addition, the companies that are used as a sample of this research have reported a sustainability report in the previous period which has an indicator similar to IR.Additionally, this study shows that IR in Indonesia is leading in reporting risks and opportunities because regulators require public companies have a risk management committee (Regulation of Bapepam and LK X.K.6). Whereas, IR in Malaysia and Singapore are leading in basic preparation and presentation of IR in behalf of the guidance of the current corporate reporting (Sustainability Reporting Guide - Malaysia and Singapore Stock Exchange) that has similar indicators to the International <IR> Framework. However, the third IR lacks the ability to disclose the strategy and allocation of resources are caused by  uncertainty. The trend for subsequent reporting will be done through IR, IR is considered capable of creating organization’s value in the short, medium, and long term to meet the needs of stakeholders.